Size reduction of poplar wood using a lathe for biofuel manufacturing: effects of biomass crystallinity on sugar yield - Zhang, Meng; Song, Xiaoxu; Pei, Zhijian J.; Deines, Timothy W.; Wang, Donghai (My University, 2014)
Poplar wood can be used as a feedstock for manufacturing cellulosic biofuel (ethanol) as an alternative to petroleum-based liquid transportation fuel. Producing biofuel from poplar wood involves reducing poplar wood into small particles (known as size reduction), hydrolyzing cellulose inside poplar particles to fermentable sugars, and converting these sugars to ethanol biofuel. Size reduction is usually done by wood chipping and biomass milling. In the literature, there are inconsistent reports about effects of particle size and biomass crystallinity on sugar yield (proportional to ethanol yield). An important reason for this inconsistence is that effects of these two biomass structural features (particle size and biomass crystallinity) on sugar yield are confounded with current size reduction methods. In this study, a lathe was used to produce poplar wood particles with (statistically) the same particle size (thickness) but different levels of biomass crystallinity, making it possible to investigate effects of biomass crystallinity on sugar yield without being confounded with effects of particle size. Results from this study show that, for the three levels of biomass crystallinity tested, sugar yield increased as biomass crystallinity decreased.
Keywords: Biofuel; Cellulosic biomass; Crystallinity; Poplar wood; Size reduction; Sugar yield